SINGV: A convective‐scale weather forecast model for Singapore. (5th October 2020) - Dipankar, Anurag; Webster, Stuart; Sun, Xiangming; Sanchez, Claudio; North, Rachel; Furtado, Kalli; Wilkinson, Jonathan; Lock, Adrian; Vosper, Simon; Huang, Xiang‐Yu; Barker, Dale
Abstract: Numerical weather prediction (NWP) capabilities in the Maritime Continent are not as developed as in the midlatitudes. Countries in the region do not develop their own modelling systems; rather they adapt models primarily developed for the midlatitudes. Due to the complexity of processes involved in the region, this adaptation is non‐trivial. In this article the developments made by the Meteorological Service Singapore (MSS) and the United Kingdom Met Office (UKMO) to implement a convective‐scale NWP system for short‐range weather prediction for Singapore and the surrounding regions are presented. In particular, this article describes the changes to the initial model configuration, which was based on the UKMO's convective‐scale NWP system (the UKV), to produce operational forecasts over this region. Results presented here demonstrate the benefit of convection‐permitting simulations over convection parametrized simulations and show that the model performance is greatly affected by the choice of driving model, the cloud scheme, and the turbulence scheme. Abstract : Numerical weather prediction (NWP) over the Maritime Continent is challenging due to complex interaction of convection with the large‐scale circulations, which are strongly affected by the land–sea breeze circulations in the region. Convection‐permitting NWP model UKV from the UK Met Office has been proven to improve forecasts over the United Kingdom and other locations. In this article, we present details of the NWP model used by the Meteorological Service Singapore, SINGV, which is adapted and subsequently modified from UKV.